Improved tolerance against helicoverpa armigera in transgenic tomato over-expressing multi-domain proteinase inhibitor gene from capsicum annuum - Tanpure, Rahul S.; Barbole, Ranjit S.; Dawkar, Vishal V.; Waichal, Yashashree A.; Joshi, Rakesh S.; Giri, Ashok P.; Gupta, Vidya S. (Physiology and Molecular Biology of Plants, 2017)
Plant proteinase inhibitors (PIs) are plant defense proteins and considered as potential candidates for engineering plant resistances against herbivores. Capsicum annuum proteinase inhibitor (CanPI7) is a multi-domain potato type II inhibitor (Pin-II) containing four inhibitory repeat domains (IRD), which target major classes of digestive enzymes in the gut of Helicoverpa armigera larvae. Stable integration and expression of the transgene in T1 transgenic generation, were confirmed by established molecular techniques. Protein extract of transgenic tomato lines showed increased inhibitory activity against H. armigera gut proteinases, supporting those domains of CanPI7 protein to be effective and active. When T1 generation plants were analyzed, they exhibited antibiosis effect against first instar larvae of H. armigera. Further, larvae fed on transgenic tomato leaves showed delayed growth relative to larvae fed on control plants, but did not change mortality rates significantly. Thus, better crop protection can be achieved in transgenic tomato by overexpression of multi-domain proteinase inhibitor CanPI7 gene against H. armigera larvae.

Identification and characterization of the key enzyme in the biosynthesis of the neurotoxin beta-ODAP in grass pea - Goldsmith, Moshe; Barad, Shiri; Knafo, Maor; Savidor, Alon; Ben-Dor, Shifra; Brandis, Alexander; Mehlman, Tevie; Peleg, Yoav; Albeck, Shira; Dym, Orly; Ben-Zeev, Efrat; Barbole, Ranjit S.; et al. (Journal of Biological Chemistry, 2022)
Grass pea (Lathyrus sativus L.) is a grain legume commonly grown in Asia and Africa for food and forage. It is a highly nutritious and robust crop, capable of surviving both droughts and floods. However, it produces a neurotoxic compound, beta-N- oxalyl-L-alpha,beta-diaminopropionic acid (beta-ODAP), which can cause a severe neurological disorder when consumed as a primary diet component. While the catalytic activity associated with beta-ODAP formation was demonstrated more than 50 years ago, the enzyme responsible for this activity has not been identified. Here, we report on the identity, activity, 3D structure, and phylogenesis of this enzyme-beta-ODAP synthase (BOS). We show that BOS belongs to the benzylalcohol O-acetyltransfer-ase, anthocyanin O-hydroxycinnamoyltransferase, anthranilate N-hydroxycinnamoyl/benzoyltransferase, deacetylvindoline 4-O-acetyltransferase superfamily of acyltransferases and is structurally similar to hydroxycinnamoyl transferase. Using molecular docking, we propose a mechanism for its catalytic activity, and using heterologous expression in tobacco leaves (Nicotiana benthamiana), we demonstrate that expression of BOS in the presence of its substrates is sufficient for beta-ODAP production in vivo. The identification of BOS may pave the way toward engineering beta-ODAP-free grass pea cultivars, which are safe for human and animal consumption.